A repunit is a number that contains only the digit 1. If 1 1 1 … 1 1 1 = 2 2 2 2 … 2 2 2 2 + ( 3 3 3 … 3 3 3 ) 2 With 1 occurring x times and 2 and 3 occurring y times then what is x / y ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A good solution.
Starting from a smaller pattern:
1 1 = 2 + 3 2 , where x = 2 , y = 1
1 1 1 1 = 2 2 + 3 3 2 , where x = 4 , y = 2
1 1 1 1 1 1 = 2 2 2 + 3 3 3 2 , where x = 6 , y = 3
This will continue forever with the pattern of y = 2 1 x
So, the answer must be y x = 2
But you must also give a genuine solution to the problem
This is a perfectly valid trollution.
I did the same way.....CHEERS!!!
even i did it this way
i madde use of G.P. 111....111(x times) = 1 + 10 + 100+ 1000 ...... and so on with finally x terms and common ratio 10 so 111....111(x times) = ((10 ^ x) - 1) / 9 thus L.H.S. = (( 10 ^ x ) - 1)/9 R.H.S. = 2*( ( 10 ^ y - 1) / 9 ) + 9 * { ( 10 ^ y - 1) / 9 } ^ 2 and solve
Simple approach is 2+3^2 is 11 so x=2 and y=1. Therefore x/y=2.
Problem Loading...
Note Loading...
Set Loading...
I solved this way:
Fist, let rewrite the second member as follows:
= 2 × y t i m e s 1 1 1 . . . 1 1 1 + 9 × ( y t i m e s 1 1 1 . . . 1 1 1 ) 2
Extracting the common factor and multiplying again we have:
= y t i m e s 1 1 1 . . . 1 1 1 × ( 2 + y t i m e s 9 9 9 . . . 9 9 9 )
But we have that y t i m e s 9 9 9 . . . 9 9 9 = 1 0 y − 1
Therefore, the second member becomes:
= y t i m e s 1 1 1 . . . 1 1 1 × ( 1 0 y + 1 )
Applying the distributive propriety, we have that
= y t i m e s 1 1 1 . . . 1 1 1 × 1 0 y + y t i m e s 1 1 1 . . . 1 1 1
= 2 y y t i m e s 1 1 1 . . . 1 1 1 y t i m e s 0 0 0 . . . 0 0 0 + y t i m e s 1 1 1 . . . 1 1 1
Wich is equal to:
= 2 y 1 1 1 . . . 1 1 1
Hence,
x 1 1 1 . . . 1 1 1 = 2 y 1 1 1 . . . 1 1 1
Finally, we must have
x = 2 × y ,
Therefore, y x = 2
Q . E . D .